Improving the Quality of Service: ETL Implementation on Data Warehouse at Pharmacy Industry - Dwi Wardhani, Fardhila Zahra; Wiratama, Jansen (Jurnal Tekno Kompak, 2024)
Pharmacy services are an important part of society and play an irreplaceable role. Availability of medicines is a key factor that needs to be considered in health services. Parapharma, as a company engaged in the supply of medicines, realizes the importance of monitoring and analyzing data to optimize medicine availability. In the ongoing process, monitoring and analyzing data related to pharmacy availability has yet to run optimally because the amount of data is quite large. The monitoring and data analysis process is still carried out conventionally, so decision-making and management of pharmacy availability still need to be optimized. Therefore, through this research, Data Warehouse and Online Analytical Processing (OLAP) will be implemented to support the decision-making process in managing pharmacy availability. The Extract, Transform, and Load (ETL) process integrates data from different sources into a data warehouse. The data is then processed and transformed so that it can be used for further analysis. By implementing a data warehouse and ETL, Parapharma can have fast and efficient access to important information contained in the data. OLAP technology, especially using Mondrian tools, is a means for companies to extract information from data warehouses with the help of interactive visualization. Various visualizations, such as information about laboratories providing the most popular pharmacy brands, the most in-demand types of pharmacys, and the average price per form of pharmacy, can provide significant insight into company strategic decisions. This research resulted in applying data warehouse and OLAP so that Parapharma can obtain accurate and detailed information regarding pharmacy demand and market trends. These research results allow companies to make the right decisions to manage pharmacy production to meet pharmacy needs efficiently. The use of data warehouse and OLAP also positively impacts improving the quality of service to the community.